The Effect of Moderate Intensity Running Exercise on Femoral Bone Microarchitectures in Ovariectomized Sprague-Dawley Rats - Sarah Hojjati; Farzad Nazem; Farhad Daryanoosh; Salman Vojdani (Fasa University of Medical Sciences, 2015)
Background & Objective: One of the most serious health problems is osteoporosis and it is mandatory to find preventive methods to confront this difficulty. Non-pharmacological methods are in priority due to less side effects. This study investigated the effect of treadmill running exercise on bone microarchitectures in female osteoporotic rats induced by ovariectomy. Materials & Methods: 30 rats were randomly divided into three groups of control, experimental one, and experimental two. Control and Experimental one (Ovariectomized) groups were kept in control conditions. The Experimental group two was subjected to 10 weeks treadmill running exercise from the 12th- post operative week. The animals were weighted in all the stages of the protocol. Finally, all rats were sacrificed and their femoral bones were removed for bone strength and bone microarchitectures analysis by using One-Way ANOVA test. The Repeated Measure was used to analyze the weight changes during the study. Results: The results showed that despite the same initial weight among groups (P=0.31), weight increased significantly in 12th and 22th postoperative weeks (P<0.001). Ovariectomy induced a significant decrease in Trabecular Thickness (TT) and Cortical Thickness (CT) (P<0.001). It also induced a weakened femoral bone strength (P=0.003). The levels of TT, CT, and bone strength increased in experimental group two compared to experimental group one and  Trabecular Separation (TS) decreased, either (P<0.001).   Conclusion: The results indicated that a moderate intensity treadmill running exercise has a protective effect on osteoporotic bones.